Design of a High-Precision ADC Test Platform Integrating STC12C5A60S2 Microcontroller and XGBoost-Based Dynamic Performance Estimation - Zhang, Hongkun; Guo, Lei; Liu, Shuanghua; Yu, Cong (Informatica, 2026)
In this paper, a high-precision analog-to-digital converter (ADC) test platform integrating both hardware and software is developed to enable accurate evaluation of ADC performance. On the hardware side, the platform employs the STC12C5A60S2 microcontroller in conjunction with the AD9833 signal generator, supported by amplification and filtering circuits, to ensure stable signal acquisition. On the software side, static parameters are extracted through statistical and time-series analysis, while a gradient boosting regression model based on XGBoost is utilized to estimate key dynamic performance metrics such as total harmonic distortion (THD). The proposed system supports both static and dynamic ADC testing and achieves high estimation accuracy with low complexity. Experimental results demonstrate that the platform can estimate THD with errors within ±2 dB for 85% of the test samples, and within ±3 dB for 92%, outperforming traditional FFT-based methods. Moreover, the effective number of bits (ENOB) deviation remains within ±0.5 bits across diverse conditions. This work provides a cost-effective and extensible solution for ADC characterization, suitable for both laboratory testing and industrial applications.